Dynamic-mechanical behaviour of anisotropic magneto-sensitive elastomers. (4th July 2018) - Ivaneyko, Dmytro; Toshchevikov, Vladimir; Saphiannikova, Marina
Abstract: The low-frequency dynamics of magneto-sensitive elastomers (MSEs) with chain-like and plane-like distributions of magnetic particles is studied under a uniform magnetic field. In this study we continue our previous work [Ivaneyko D. et al., Soft Matter, 2015, 11, 7627–7638], in which a coarse-grained cubic network model was proposed for description of the dynamic-mechanical behaviour of isotropic MSEs. Presently, to describe the dynamics of MSEs with anisotropic particle distributions, we use a tetragonal lattice model, in which average distances between neighbouring particles along and perpendicular to the symmetry axis of an MSE may differ. Effects of the elastic network and magnetic interactions between the magnetic particles on the dynamics are taken into account. Application of the magnetic field H along the symmetry axis of MSE leads to a strong anisotropy of the dynamic storage G ' and loss G ″ moduli, which depend on the geometry of the applied shear strain with respect to H . The change of dynamic moduli under the magnetic field is more pronounced for MSEs with anisotropic particle distributions as compared to isotropic MSEs. G ' and G ″ can change up to several orders of magnitude in agreement with recent experiments. Graphical abstract: Image 1 Highlights: Coarse-grained model of anisotropic magneto-sensitive elastomers (MSEs) is proposed. Dynamics of MSEs with chains and planes formed by magnetic particles is studied. Characteristic power-law behaviour is predicted for strongly anisotropic MSEs. Magnetic field splits the dynamic moduli into three principal values depending on shear geometry. The 20-fold field-induced increase of the moduli agrees well with experiments.